2017
DOI: 10.1111/lnc3.12239
|View full text |Cite
|
Sign up to set email alerts
|

Neurobiological bases of reading disorder Part I: Etiological investigations

Abstract: While many studies have focused on identifying the neural and behavioral characteristics of decoding-based reading disorder (RD, aka developmental dyslexia), the etiology of RD remains largely unknown and understudied. Because the brain plays an intermediate role between genetic factors and behavioral outcomes, it is promising to address causality from a neural perspective. In the current, Part I of the two-part review, we discuss neuroimaging approaches to addressing the causality issue and review the results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 119 publications
(150 reference statements)
0
17
0
1
Order By: Relevance
“…Several susceptibility genes have been identified ( 8 ), though each explains only a small fraction of variance, suggesting the involvement of other mechanisms including polygenicity, epistasis, and epigenetics, in RD ( 9 ). Neuroanatomical anomalies in both gray and white matters shown to be causally related to RD ( 10 ) are observed in areas and networks associated with phonological, orthographic, and articulatory processing ( 11 13 ). Additionally, work in neural oscillations as well as neurochemistry shows deficits related to sensory processing, particularly auditory discrimination, in individuals with or at-risk for RD ( 14 , 15 ).…”
Section: Methodsmentioning
confidence: 99%
“…Several susceptibility genes have been identified ( 8 ), though each explains only a small fraction of variance, suggesting the involvement of other mechanisms including polygenicity, epistasis, and epigenetics, in RD ( 9 ). Neuroanatomical anomalies in both gray and white matters shown to be causally related to RD ( 10 ) are observed in areas and networks associated with phonological, orthographic, and articulatory processing ( 11 13 ). Additionally, work in neural oscillations as well as neurochemistry shows deficits related to sensory processing, particularly auditory discrimination, in individuals with or at-risk for RD ( 14 , 15 ).…”
Section: Methodsmentioning
confidence: 99%
“…There have been several neuroimaging studies of dyslexia using functional magnetic resonance imaging (fMRI), in which groups of participants with reading difficulties are compared to groups of participants with no difficulties. The results have been summarized in recent reviews (e.g., [ 47 , 48 ]; see also [ 49 , 50 , 51 , 52 , 53 ]). The actual picture from the individual research papers is much noisier than the brief summaries in the reviews might lead one to assume, with many unreliable findings, unreplicated across studies, most likely due to the typically small sample sizes and, possibly, in part due to differences between tasks, sampling criteria, languages, equipment, and statistical analysis software.…”
Section: Functional Neuroimaging Of Dyslexiamentioning
confidence: 99%
“…The occipitotemporal (including the visual word form area; VWFA), temporoparietal, and left frontal regions regularly emerge in fMRI studies on dyslexia and are identified as important core regions for reading [ 1 , 15 •, 19 22 ]. Temporoparietal cortex (TPC) activation is often found in studies (and meta-analyses), although with some limitations.…”
Section: Brain Activation Abnormalitiesmentioning
confidence: 99%
“…In most classic accounts of brain abnormalities in dyslexia, the importance of the left temporoparietal cortex is especially highlighted, since this brain region has been closely linked with the phonological processing deficits in dyslexia [ 13 , 14 , 15 •]. Although left ventral posterior occipitotemporal dysfunctions are regularly discussed, those were often seen as secondary brain deficits in dyslexia, as it was assumed that phonological processing deficits reflected in temporoparietal dysfunctions would cause disrupted development of the left occipitotemporal cortex (OTC).…”
Section: Introductionmentioning
confidence: 99%